Diseño De Un Modelo De Gestión Para El Adecuado Control De Las Cuentas Y Documentos Por Cobrar Y Pagar En El Almacén D´L Malecón De La Ciudad De Vinces En La Provincia De Los Ríos... - Pino Carpio, María (2014)
This paper aims to study the management of accounts receivable and payable Warehouse D'L MALECÓN through a diagnosis of the current situation, the proper restructuring knowledge of information pertaining to accounts receivable in the development of research design management model was determined, for which the creation of this was raised, being an efficient system for proper operation and control of these accounts, in order to achieve a timely return financial resources and reducing store credit losses...